OLS estimation of the intra-household distribution of expenditure - Valérie Lechene; Krishna Pendakur; Alex Wolf (Institute for Fiscal Studies (IFS), 2021)
We provide a method to estimate resource shares - the fraction of total household expenditure allocated to each household member - using OLS estimation of Engel curves. The method is a linear reframing of the nonlinear model of Dunbar, Lewbel and Pendakur (2013), extended to allow single-parent and other complex households, scale economies in assignable goods and complementarities between non assignable goods, and supplemented with a linear identification test. We apply the model to data from 12 countries, and investigate resource shares, gender gaps, and poverty at the individual level. We reject equal sharing, and find large gender gaps in resource shares, and consequently in poverty rates, in some countries.
Keywords: D13; D63; I32; 330; collective households; resource shares; intra-household inequality; poverty